ANALISIS TINGKAT KEPUASAN PASIEN RAWAT INAP RUMAH SAKIT ISLAM SULTAN AGUNG SEMARANG DILIHAT DARI DIMENSI KUALITAS PELAYANAN - Utama, Puspa Yudha; Prihartini, Apriatni Endang; Listyorini, Sari (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2013)
Competition occurs among private hospitals make patient satisfaction a top priority, which will be fulfilled when the patient satisfaction of services provided in accordance with their expectations. Therefore, hospitals need to assess what are the factors that will affect patient satisfactions and patient satisfactions are met in order to maintain the patients. This study aimed to analyze the level of patient satisfaction at RSI Sultan Agung Semarang seen from the dimensions of service quality. The hypothesis, there are differences in quality service for hospitalized patients in each class. This type of research in this research is explanatory research with a number of respondents 120 respondents were taken using proportionate stratified sampling technique. The method of analysis used in this study is the Importance Performance Analysis (IPA) Based on the analysis of the IPA, found that for the VIP class, I class, II class, and III class have different attributes in Quadrant A, Quadrant B, Quadrant C, and Quadrant D. From the analysis of patient satisfaction showed that the overall level of patient satisfaction in VIP class and I class in the category of satisfied. While the level of satisfaction of hospitalized patients in class II and class III in the category of very satisfied. RSI Sultan Agung Semarang advised to maintain and improve service performance attributes in Quadrant A.